The The Effect of Sustainable Financial Policy Implementation on Banking Performance in Indonesia - Adilah Permananingrum; Riskon Ginting; Ahmad Sutanto; Arif Santoso; Husnil Barry (University of Merdeka Malang, 2026)
The implementation of sustainable finance has become an important policy instrument in encouraging the transformation of the financial sector toward sustainable economic development. In Indonesia, Peraturan OJK No.51/POJK.03/2017 was introduced to strengthen the integration of environmental, social, and governance principles within the financial services industry, particularly the banking sector. However, empirical evidence regarding the impact of this policy on banking performance in emerging economies remains limited. This study aims to examine the effect of sustainable finance policy implementation on banking performance in Indonesia and to identify the mechanisms through which the policy affects bank performance. This study employs a quantitative approach using the Difference-in-Differences method on a sample of BUKU 3 and BUKU 4 banks in Indonesia during the 2015–2024 period. Banking performance is measured using Net Interest Margin. In addition, this study investigates the mediating role of green credit ratio and operational efficiency proxied by Operating Expense Ratio. The findings indicate that the implementation of sustainable finance policy has a positive and significant effect on banking performance. The results further show that the green credit ratio significantly mediates the relationship between policy implementation and bank performance. However, operational efficiency measured by BOPO does not show a significant mediating effect. The study concludes that sustainable finance policy implementation contributes positively to banking intermediation performance, particularly through the expansion of green financing. These findings suggest that sustainable finance is not only a regulatory obligation but also a strategic opportunity to improve banking performance in Indonesia.